Breast cancer metastasis and drug resistance - Ahmad, Aamir (New York Springer, 2013)
This volume comprehensively covers recent prrogress in breast cancer research. In an effort to successfully treat breast cancer, it is imperative to fully understand the disease with all its heterogeneity ; understand the factors that influence the metastasis of breast cancer to distant organs making it lethal and understand the underlying processes that lead to the phenomenon of drug-resistance making the disease particularly incurable. The book explores all of these issues, including the phenomenon of epithelial-mesenchymal-transition, cancer stem cells as well as microRNAs in an attempt to better understand the disease in connection to its heterogeneity, metastasis, drug-resistance as well as to propose novel signaling pathways for therapeutic intervention. The profiling of tumors to molecularly classify breast cancers is also investigated so that customized targeted therapies can be developed --
Keywords: Breast; Drug resistance in cancer cells; Breast Neoplasms; Drug Resistance, Neoplasm; Neoplasm Metastasis